1990
DOI: 10.1093/her/5.2.125
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for developing and evaluating behavior change interventions for injury control

Abstract: This paper addresses issues and research needs in the domain of behavior modification for injury control. Although much of the discussion focuses on traffic safety, the concepts and principles are applicable to all areas of injury control (e.g. on the job and in the home). Field research that has increased safety belt use is reviewed briefly to illustrate a tripartite classification of injury control factors (i.e. environmental, individual, or behavioral variables), and to introduce a heuristic framework for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 31 publications
(10 reference statements)
0
54
0
1
Order By: Relevance
“…Such interventions have typically targeted many of the individual-level factors (or the individual's immediate environment) reviewed in this paper. Interventions have ranged from so-called "antecedent strategies" aimed at changing the factors that precede consumer behavior-such as basic information provision and education; goal-setting and commitment strategies; and the use of social/group norms, peer influence and social modeling-through to more "consequence" strategies aimed at changing the outcomes of such behavior-such as self-monitoring; delivering feedback (on one's behavior or performance); and the use of rewards (intrinsic and extrinsic) and other incentives [14,165]. While the literature suggests that all of these strategies have the potential to motivate pro-environmental behavior, the effects have been far from robust and consistent across studies-certain strategies have been found to be effective in some contexts, for some people, and for some types of behavior, but not others (for an overview, see [166]).…”
Section: Practical Implications and Directions For Future Researchmentioning
confidence: 99%
“…Such interventions have typically targeted many of the individual-level factors (or the individual's immediate environment) reviewed in this paper. Interventions have ranged from so-called "antecedent strategies" aimed at changing the factors that precede consumer behavior-such as basic information provision and education; goal-setting and commitment strategies; and the use of social/group norms, peer influence and social modeling-through to more "consequence" strategies aimed at changing the outcomes of such behavior-such as self-monitoring; delivering feedback (on one's behavior or performance); and the use of rewards (intrinsic and extrinsic) and other incentives [14,165]. While the literature suggests that all of these strategies have the potential to motivate pro-environmental behavior, the effects have been far from robust and consistent across studies-certain strategies have been found to be effective in some contexts, for some people, and for some types of behavior, but not others (for an overview, see [166]).…”
Section: Practical Implications and Directions For Future Researchmentioning
confidence: 99%
“…A key proposition in the multiple intervention level model proposed by Geller et al (1990) and refined by Geller (1992) is that individuals influenced by an intervention program (at a particular level of cost effectiveness and intrusiveness) should not be targeted for further intervention, but rather should be enrolled as intervention agents for the next (i.e., higher) level of behavior change intervention. In other words, "preaching to the choir" is not as beneficial as enlisting the "choir" to preach to others (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the six correlations (i.e., risky lifestyles at both sites and cognitive failures at Site 1) were not significant. Geller et al (1990) introduced a system for categorizing behavior change techniques and developing a more systematic approach to designing intervention programs to fit a particular behavioral problem, target audience, and organizational culture (see also Geller, 1992). Interventions were categorized into multiple levels or tiers, each level defined by its intrusiveness and cost-effectiveness.…”
Section: Convergent and Divergent Validitymentioning
confidence: 99%
“…Subsequently, De Young (1996) argued that durable proenvironmental changes can be facilitated by devising techniques that combine (a) detailed procedural information, (b) feedback about one's performance, and (c) a supportive social environment. Similar conditions to increase intervention effectiveness were proposed by Geller et al (1990). Geller (2002, p.534) incorporated these intervention elements in a scheme, the "flow of behavior change" model, that described how to move an individual through the stages in which environmentally unfriendly habits are changed into environmentally friendly behavior and ultimately into environmentally friendly habits.…”
Section: The Effectiveness Of Interventions To Promote Proenvironmentmentioning
confidence: 99%